DISCIPLINE INFLUENCE THE PEFORMANCE OF TEACHER WORKING PUBLIC PRIMARY SCHOOLS JUNIOR HIGH SCHOOL MANDAU KABUPATEN BENGKALIS - Putra, Eka (Jurnal Niara, 2019)
This research was conducted at junior school 8 Mandau Kecamatan Mandau. The purpose of this study was to determinance the effect of discipline influance the performance of teacher working in the office Mandau.The population in this were 45 teacher. In this study the sampling using saturated sample. Is aqual to 45 teacher. Data analysis in this research use descriptive and quantitative method.The result showed that the discipline of positive and significant of teacher working. The amount of influence of teacher working is disciplined by 53,9 percent while the rest 46,1 percent describing other independent variables that are not observed in this study.Recommendation can be submitted to the public junior School 8 Mandau Kecamatan Mandau, for even more attention is disciplined, this is because the disciplined has agreat influance, that is 53,9 percent.